Comparison of predicting the severity of disease by clinical and radiological scoring systems in acute pancreatitis - ÖZPOLAT, ÇİĞDEM; AKOĞLU, HALDUN; DENİZBAŞI ALTINOK, ARZU (My University, 2022)
Aim: Acute pancreatitis (AP) is a frequent reason for patient presentation in emergency department. It is hard to assess objectively the grade of the disease due to a wide range of clinical signs in terms of determination the need for intensive care or surgical intervention. At this stage there is not a unique, unified scoring system that determines the severity of the disease. In this study we aimed to compare clinically used AP scoring systems; Ranson, BISAP and Balthazar (CTSI), SIRS to predict disease severity. Material and Methods: In this study, AP patients that were diagnosed by Atlanta criteria were analyzed retrospectively. The clinical, laboratory and radiological images and results of the patients were analyzed by using the "first 24 hours Ranson", "BISAP" and SIRS scores. The Balthazar scores were calculated from the CT reports retrospectively. Results: Age, respiratory rate and BUN values of the patients with mortality were significantly higher than the patients who survived, whereas diastolic blood pressure, systolic BP blood pressure, SO2 and amylase values of the patients with mortality were found to be significantly lower than the patients who survived. When the 6 month mortality prediction of prognostic scoring systems was examined, it was found that the BISAP score could catch 94% of mortality (95% CI: 0.88-0.97), and the SIRS score could predict mortality by 74.7% (95% CI: 0,66-0,82). Conclusion: Regarding the APs severity prediction, BISAP and SIRS scores were more sensitive and specific in terms of monthly and overall mortality in patients

Amaç: Akut pankreatit (AP) acil servis hasta başvurularının önemli nedenlerinden biridir. Çok çeşitli klinik belirtiler nedeniyle yoğun bakım veya cerrahi müdahale ihtiyacının belirlenmesi açısından hastalığın derecesini objektif olarak değerlendirmek zordur. Şu an, hastalığın şiddetini belirleyen mükemmel bir puanlama sistemi yoktur. Bu çalışmada hastalık şiddetini tahmin etmek için klinik olarak kullanılan AP skorlama sistemleri olan Ranson, BISAP ve Balthazar (CTSI), SIRS skorlamalarını karşılaştırmayı amaçladık. Gereç ve Yöntemler: Bu çalışmada Atlanta kriterlerine göre tanı konulan AP hastaları retrospektif olarak incelendi. Hastaların klinik, laboratuvar sonuçları ve radyolojik görüntüleri kullanılarak "ilk 24 saat Ranson", "BISAP" ve SIRS skorları analiz edildi. Balthazar skorları geriye dönük olarak BT raporlarından hesaplandı. Bulgular: Mortal seyreden hastaların yaş, solunum hızı ve BUN değerleri, hayatta kalanlara göre anlamlı olarak yüksek bulunurken, mortalitesi olan hastaların diyastolik kan basıncı, sistolik kan basıncı, SO2 ve amilaz değerleri anlamlı olarak düşük bulundu. Prognostik skorlama sistemlerinin 6 aylık mortalite tahmini incelendiğinde BİSAP skorunun mortalitenin %94'ünü yakalayabildiği (%95 GA: 0.88-0.97), SIRS skorunun mortaliteyi %74,7 (%95 CI: 0,66-0,82) öngörebildiği bulundu. Sonuç: Hastalarda AP şiddeti tahmini ile ilgili olarak BİSAP ve SIRS skorları aylık ve genel mortalite açısından daha duyarlı ve spesifikti.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Acute pancreatitis; BISAP; Balthazar; Ranson; Akut pankreatit